Financial implications of diversity and inclusion initiatives on employee work behavior in the polymer industry - Sharma, Shagun; Ujjawal, Nishtha; Gupta, Manisha; Yahya, M. Z. A.; Noor, I. M.; Yusuf, S. N. F.; Abdul Latif, Famiza; Shyam, Hari Shankar (John Wiley and Sons, 2025)
This research uses the Knowledge, Attitude, Practice (KAP) model to assess the financial consequences of diversity and inclusion (D&I) programs on employee work behavior in the polymer industry. The study investigates the impact of integrating the KAP framework on organizational performance and financial results by analyzing the effects of improved awareness of D&I principles, positive attitudes towards inclusive practices, and the execution of D&I policies. The study utilizes both quantitative and qualitative data collected from various polymer industries. It evaluates characteristics such as innovation output, productivity measures, and personnel turnover rates. Initial results indicate that companies with strong diversity and inclusion programs see enhanced financial results, which may be linked to a well-informed, positive-minded, and actively involved staff. The study recognizes the limitations of isolating the influences of diversity and inclusion (D&I) from other financial factors, the focus on mostly large-scale businesses, and the need for longitudinal data to accurately measure long-term financial effects. However, it still provides evidence of the positive economic impact of D&I. The results provide valuable insights into how diversity and inclusion programs may be strategically used in the polymer sector to improve financial performance.